Processos de Recuperação de Cobalto e de Lítio de Baterias de Íons de Lítio - Urias, Patrícia Moisés (2017)
Li-ion batteries should be recycled not only for environmental reasons, but also this type of waste represents an important secondary source of metals. This work aimed to evaluate the recovery of Co and Li metals from Li-ion batteries. For leaching, preliminary steps were carried out with three types of leachate: H2SO4 (2M), photofermentation effluent (0.75M) with addition of organic acids (lactic, acetic, butyl and propionic acids) totaling a concentration of 3.4 M and mixture of photofermentation effluent (0.75 M) + H2SO4 (1.25 M). In addition, the action of H2O2, glucose and lactose as reducing agents under varying temperature conditions (60 ° C and 90 ° C) and leaching time (1 h and 3 h) were analyzed. From the results, a Central Composite Planning (CCP) 2³ was established for the following variables and their respective ranges: solid/liquid ratio (20 g/L - 40 g/L), temperature (70 ºC – 90 ºC) and (1h - 3h), whose optimum point was 86 ºC, 18.5 g/L and 2.5 h, with Co and Li recovery of 93,13 % and 93,90 %, respectively. Based on this process condition, a CCP 2² was prepared to evaluate the following variables: lactose concentration from the whey permeate (0.01 M - 0.17 M) and agitation (320 rpm - 580 rpm), obtaining the best result was the lactose concentration of 0.09 M and agitation of 300 rpm, reaching recovery rates of 93.35 % for Co and 90.50 % for Li. In order to evaluate the effect and comparing its influence on leaching, in a process based on the previously defined conditions, the ultrasonic agitation was carried out, obtaining a lower recovery of 63.32 % of Co and 63.64 % of Li.